Preparation method of sulfonated polyetheretherketone-based composite proton exchange membrane with low sulfonation degree
By combining the low-sulfonation sulfonated polyether ether ketone with a sulfonate-rich porous organic framework, a proton exchange membrane with high proton conductivity, low swelling rate and high ion exchange capacity was prepared, which solved the problem of swelling and insufficient performance of the existing membrane at high temperatures.
Patent Information
- Application Number
- CN202411908578.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The existing sulfonated polyether ether ketone proton exchange membranes are prone to excessive swelling at high temperatures, resulting in a decrease in mechanical properties and insufficient proton conductivity and ion exchange capacity.
The composite preparation method of low-sulfonation sulfonated polyether ether ketone (SPEEK) and sulfonate-rich porous organic frame (SNK-41) was adopted to prepare a composite proton exchange membrane by solution casting. The high specific surface area of SNK-41 and the sulfonic acid group were used to improve the proton conductivity, and the low swelling rate was maintained under high humidity.
The high proton conductivity, high ion exchange capacity and low swelling rate of the composite proton exchange membrane are achieved, avoiding the swelling problem of high sulfonation film, and improving the stability and performance of the membrane.
Smart Images

Figure CN119725645A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, in particular to the field of fuel cell proton exchange membranes, and is a method for preparing a low-sulfonation-degree sulfonated polyetheretherketone-based composite proton exchange membrane. Background Art
[0002] Hydrogen energy is an ideal clean energy in the 21st century. It has the characteristics of high energy density, zero emission and renewable. Compared with other energy materials, it is cleaner and more efficient and will become the main force of future development. Compared with combustion, fuel cells can convert hydrogen energy and other chemical energy into electrical energy with their simple and efficient electrode reaction mode, without the need for cumbersome transformation process, and have a high conversion rate. It is an excellent way to utilize hydrogen energy. Proton exchange membrane fuel cells have the advantages of high efficiency, environmental protection and energy saving, and have great potential in the fields of automobiles and drones. Among them, as an important component of proton exchange membrane fuel cells, the proton transfer performance of polymer proton exchange membrane (PEM) directly determines the performance of the entire fuel cell stack. In addition to meeting the requirements of high proton conductivity and excellent fuel isolation performance, proton exchange membranes must also adapt to the diverse working environment of proton exchange membrane fuel cells, including: maintaining high durability, good fracture strength, dimensional stability and chemical stability in extreme temperature, humidity and chemical environment, and also need to have processing feasibility and be competitive in cost-effectiveness. The commercial application of proton exchange membranes places extremely high demands on these performance indicators of proton exchange membranes.
[0003] Sulfonated polyetheretherketone is considered by researchers to be a potential proton exchange membrane material due to its good heat resistance and mechanical properties. Its proton conductivity and proton exchange capacity increase with the increase of sulfonation degree, but with the increase of sulfonation degree, the swelling rate of sulfonated polyetheretherketone increases and the mechanical properties decrease. Patent 202311131599.8 provides a method for preparing a composite proton exchange membrane of sulfonated polyetheretherketone and ketoenamine covalent organic framework material. The patent mixes sulfonated polyetheretherketone with the first monomer of ketoenamine covalent organic framework material, adds the second monomer to obtain a mixture of sulfonated polyetheretherketone and covalent organic framework, and then forms a membrane to obtain a composite proton exchange membrane. However, the sulfonated polyetheretherketone used has a high degree of sulfonation and there is a risk of excessive swelling. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a low-sulfonation degree sulfonated polyetheretherketone-based composite proton exchange membrane in view of the limitations of the above-mentioned prior art. The method uses the addition reaction of 1,3-propane sultone and NK-COF-41 to synthesize a sulfonic acid group-rich porous organic framework, which is then mixed with SPEEK to prepare a low-sulfonation degree SPEEK / sulfonic acid group-rich porous organic framework composite proton exchange membrane by solution casting; the sulfonic acid group-rich porous organic framework obtained by the present invention not only has 468.6m 2 g -1 It has a high specific surface area and a sulfonation degree of nearly 90%, which can provide abundant active sites for the transfer of protons. At the same time, its structure is stable and it hardly swells at 80°C and 100% RH. The prepared composite proton exchange membrane has the characteristics of high proton conductivity, high ion exchange capacity and low swelling rate.
[0005] The technical solution of the present invention is:
[0006] A method for preparing a low-sulfonation degree sulfonated polyetheretherketone-based composite proton exchange membrane comprises the following steps:
[0007] Step 1, Synthesis of sulfonic acid-rich porous organic framework (SNK-41):
[0008] Take two reaction tubes, add acetonitrile and NK-COF-41 to reaction tube A, and add acetonitrile and 1,3-propane sultone to reaction tube B; under nitrogen protection, add the solution in tube B dropwise to tube A, and then reflux in a 60-80°C water bath for 12-24 hours; filter the reaction product, wash the filter cake with acetonitrile, and vacuum dry to obtain a red powder solid, which is recorded as SNK-41;
[0009] In which, in reaction tube A, 200-300 mg of dried NK-COF-41 was added to every 10 mL of ultra-dry acetonitrile; in reaction tube B, 200-300 mg of 1,3-propane sultone was added to every 10 mL of ultra-dry acetonitrile; the mass ratio of NK-COF-41 to 1,3-propane sultone was 4:5;
[0010] The NK-COF-41 is obtained by vacuum drying after ball milling; the rotation speed of the ball mill is 500-1000rpm, and the time is 5-18h; the drying temperature is 40-80℃, and the time is 6-24h.
[0011] Step 2, ball-milling the SNK-41 powder obtained in step 1, sieving it, adding it to N,N-dimethylacetamide (DMAc), and ultrasonically dispersing it to obtain a SNK-41 dispersion;
[0012] Among them, 380-480 mg of SNK-41 powder was added to every 4 mL of DMAc;
[0013] Step 3, adding the SNK-41 dispersion obtained in step 2 dropwise into the low-sulfonation-degree SPEEK dispersion, and stirring and mixing at room temperature to obtain a mixed solution;
[0014] The concentration of SPEEK dispersion is 100-120 mg mL -1 , the solvent is DMAc; the mass ratio is, SNK-41 dispersion: SPEEK dispersion = (0.1-0.4): 1;
[0015] Step 4, coating the mixed solution obtained in step 3 on a glass plate, vacuum drying at 40-60° C. for 6-24 hours, then vacuum drying at 70-90° C. for 12-24 hours, and finally annealing in a vacuum drying oven at 110-120° C. for 3-6 hours; after cooling to room temperature, peeling the composite membrane from the glass plate with ultrapure water to obtain a sulfonated polyetheretherketone / sulfonic acid-rich porous organic framework composite proton exchange membrane.
[0016] The sulfonation degree of the low-sulfonation-degree SPEEK is 45%-55%.
[0017] The thickness of the sulfonated polyetheretherketone / sulfonic acid group-rich porous organic framework composite proton exchange membrane is 16-60 μm.
[0018] The sulfonated polyetheretherketone / sulfonic acid-rich porous organic framework composite proton exchange membrane has a proton conductivity of 0.121S cm at 80°C and 100% RH. -1 -0.163S cm -1 .
[0019] The essential features of the present invention are:
[0020] The present invention first selects low-sulfonation degree sulfonated polyetheretherketone (SPEEK) as the polymer proton exchange membrane base membrane, fully utilizes the advantages of low-sulfonation degree polyetheretherketone base membrane with excellent dimensional stability, oxidation stability and mechanical properties, and avoids the problem of high-sulfonation degree polyetheretherketone base membrane excessive swelling at high temperature; then improves the proton transfer performance of the low-sulfonation degree SPEEK membrane, introduces a sulfonic acid group-rich porous organic framework (SNK-41) as a filler into the base membrane, and finally obtains the high-sulfonation degree polyetheretherketone base membrane with high proton conductivity, and also avoids the low proton conductivity defect of the low-sulfonation degree polyetheretherketone base membrane.
[0021] The mechanism is as follows: 1,3-propane sultone is ring-opened and reacts with the pyridine N atom of NK-COF-41 to synthesize the sulfonic acid-rich porous organic framework SNK-41. SNK-41 has a sulfonation degree of up to 90%, and the rich sulfonic acid groups provide sufficient sites for proton transfer. At the same time, SNK-41 has a 468.6m 2 g-1 The high specific surface area of SNK-41 can build a continuous hydrogen bond network after full hydration, which promotes the transport of protons by the Gaossian mechanism. In addition, SNK-41 has a stable structure and hardly swells at 80°C and 100% RH. After being compounded with the low-sulfonation SPEEK matrix, it can effectively reduce the swelling rate of the composite proton exchange membrane. Therefore, the SPEEK@SNK-41 composite proton exchange membrane has the characteristics of high proton conductivity, high ion exchange capacity and low swelling rate.
[0022] The beneficial effects of the present invention are:
[0023] The low-sulfonation-degree sulfonic acid-rich SPK@SNK-40% composite proton exchange membrane prepared by the present invention has a high proton conductivity (0.163S cm at 80°C and 100% RH). -1 ), low surface swelling rate (11.7% at 80°C, 100% RH), high ion exchange capacity (2.05 meq g at 80°C, 100% RH) -1 ) and other properties. Compared with the SPK45 base membrane with the same sulfonation degree but not compounded with sulfonic acid-rich groups, the proton conductivity increased by 73%, the ion exchange capacity increased by 20%, and compared with the SPEEK proton exchange membrane with a high sulfonation degree (the sulfonation degree in the present invention is 68%), the surface swelling rate was reduced from 136.2% to 11.7%. In the stability test within 28 days, the proton conductivity of the SPK45 base membrane without compounding sulfonic acid-rich porous organic framework filler was only 28.1% of the initial value, and the low sulfonation degree sulfonic acid-rich SPK45@SNK-40% still had 79.9% of the initial proton conductivity, and the stability was the same under the same conditions. 96.8% of 117. Therefore, the low-sulfonation degree SPEEK sulfonic acid group-rich covalent organic framework composite proton exchange membrane prepared in the present invention has the characteristics of high ion exchange capacity, high proton conductivity, low surface swelling rate, high stability, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The proton conductivity of the SPK45-based composite proton exchange membrane obtained in Examples 1-4 and Comparative Example 1 at different temperatures;
[0025] Figure 2 The proton conductivity stability of the composite proton exchange membranes obtained in Example 1 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific implementation described herein is only used to explain the present invention and is not intended to limit the present invention.
[0027] The low sulfonation degree SPEEK@sulfonic acid group-rich porous organic framework composite proton exchange membrane proposed in the present invention is prepared by solution casting method with low sulfonation degree SPEEK as substrate and sulfonic acid group-rich porous organic framework powder as filler. The preparation process mainly includes: preparation of low sulfonation degree SPEEK, preparation of sulfonic acid group-rich porous organic framework (SNK-41), and preparation of SPK@SNK-X composite membrane. The SPEEK substrate is prepared by post-sulfonation method, and the sulfonic acid group-rich porous organic framework SNK-41 is prepared by one-pot method; the prepared SPEEK and SNK-41 powders are respectively uniformly dispersed in DMAc solvent to obtain SPEEK and SNK-41 solutions respectively; after the two solutions are blended, the sulfonated polyetheretherketone / sulfonic acid group-rich porous organic composite proton exchange membrane is prepared by solution casting method. The proton exchange membrane has excellent proton conductivity and low swelling rate. The preparation method of the present invention is temperature-controlled, simple and efficient. The prepared proton exchange membrane has high proton conductivity and excellent fracture strength, as well as good thermal, chemical and long-term use stability, which is conducive to its wide application in hydrogen energy conversion technology.
[0028] The NK-COF-41 described in the present invention is a known material with a purity of 98%, and is produced by Beijing Huawei Ruike Chemical Co., Ltd.
[0029] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. However, the following examples are only for illustration and should not be considered as any limitation to the present invention.
[0030] Example 1
[0031] The steps for preparing the SPK@SNK composite proton exchange membrane are as follows:
[0032] Step 1, preparation of low sulfonation degree SPEEK: First, remove the water from the polyetheretherketone (PEEK) raw material at 60°C under vacuum conditions. Under ice-water bath conditions, take 7g of dry PEEK and add it to 120mL 98% concentrated sulfuric acid, then use a double-row tube to repeat the vacuum-nitrogen flushing process for the reaction bottle at least three times, and seal the bottle mouth with an acid-resistant rubber stopper, and stir with strong magnetic force (1000rpm) for 6h until dissolved. Then heat to 60°C for heating sulfonation reaction for 55min, and then slowly pour the reaction product into a large amount of ice water with mechanical stirring to obtain white filamentous SPEEK. Then wash SPEEK with a large amount of deionized water to pH=7.0, dry to obtain yellow SPEEK, and the obtained SPEEK sulfonation degree is 45% by nuclear magnetic resonance hydrogen spectrum test, recorded as SPK45.
[0033] The specific reaction formula of the sulfonation reaction is as follows:
[0034]
[0035] Step 2, preparation of sulfonic acid-rich porous organic framework SNK-41: At room temperature, the raw material NK-COF-41 was ball-milled for 12 hours (speed of 500-1000rpm), and then placed in a vacuum oven at 80°C for 24 hours. Under ice-water bath conditions, 10mL of ultra-dry acetonitrile (purity of more than 99.99%, water content of less than 0.01%) was added to two 50mL dry pressure-resistant reaction tubes A and B, respectively, and 200mg of dried NK-COF-41 was added to tube A, and ultrasonicated until uniformly dispersed. Take 250mg of 1,3-propane sultone and add it dropwise to tube B, and ultrasonicate until uniformly dispersed. Reaction tubes A and B were vacuumed and flushed with nitrogen at least three times with double-row tubes. Under nitrogen protection, the solution in tube B was slowly added dropwise to the dispersion in tube A, and then reacted in a water bath at 80°C for 12 hours. The reaction product was filtered and repeatedly washed with acetonitrile to remove unreacted 1,3-propane sultone, and dried in a vacuum oven at 60° C. to constant weight to obtain a red powder solid, namely SNK-41.
[0036]
[0037] The sulfonation degree of SNK-41 was 90% as determined by H NMR spectrum test, and its specific surface area was 468.6 m 2 g -1
[0038] The obtained sulfonic acid group-rich porous organic framework material has the following advantages: (1) The physical and chemical stability of the porous organic framework itself enables it to adapt to the working conditions of the fuel cell without swelling or decomposition; (2) The large number of sulfonic acid groups in the sulfonic acid group-rich porous organic framework can serve as proton carriers to promote the transport of protons; (3) The sulfonic acid group-rich porous organic framework has an open space network structure with a high specific surface area, which can construct a complex microphase structure inside the membrane, including the inside of the porous organic framework and between the porous organic framework and the proton exchange membrane matrix. In short, the composite of the sulfonic acid group-rich porous organic framework and low-sulfonation degree SPEEK can provide abundant sites for proton transport, reconstruct the microphase structure in the membrane, improve the connectivity of the proton transport channel in the membrane, improve the proton transfer performance, and effectively reduce the swelling of the proton exchange membrane.
[0039] Step 3: Preparation of SPK@SNK composite proton exchange membrane: SPEEK prepared in step 1 and N,N-dimethylacetamide (DMAc) were prepared to a mass volume concentration of 120 mg mL -1The dispersion was stirred at room temperature until completely dissolved. The SNK-41 powder prepared in step 2 was ball-milled and passed through a 150-mesh sieve. 400 mg of the sieved powder was weighed and dispersed in 4 mL of DMAc and ultrasonicated for 12 hours to ensure uniform dispersion. The SNK-41 dispersion and the SPEEK dispersion were fully mixed at a mass ratio of 0.4:1. The mixed solution was evenly dropped on a 5 cm × 5 cm glass plate by solution casting, dried in a vacuum drying oven at 60 ° C for 12 hours, then dried in a vacuum drying oven at 80 ° C for 12 hours, and finally annealed in a vacuum drying oven at 120 ° C for 3 hours. After cooling to room temperature, the composite membrane was peeled off from the glass plate with ultrapure water to obtain SPEEK@SNK composite membrane 1 with a thickness of 40 μm, recorded as SPK45@SNK-40%.
[0040] The proton conductivity of the composite membrane 1 was tested using an electrochemical workstation. At 80°C and 100% relative humidity, the proton conductivity was 0.163 S cm -1 .
[0041] Example 2
[0042] A low-sulfonation degree SPEEK@sulfonic acid-rich porous organic framework composite proton exchange membrane was prepared. The preparation process was basically the same as that in Example 1, except that in step 3, the mass ratio of SNK-41 dispersion to SPEEK dispersion was changed from 0.4:1 to 0.3:1 to finally obtain SPEEK@SNK composite membrane 2, recorded as SPK45@SNK-30%.
[0043] The proton conductivity of composite membrane 2 was tested using an electrochemical workstation. At 80°C and 100% relative humidity, the proton conductivity was 0.141 S cm -1 .
[0044] Example 3
[0045] A low-sulfonation degree SPEEK@sulfonic acid-rich porous organic framework composite proton exchange membrane was prepared. The preparation process was basically the same as that in Example 1, except that in step 3, the mass ratio of SNK-41 dispersion to SPEEK dispersion was changed from 0.4:1 to 0.2:1 to finally obtain SPEEK@SNK composite membrane 3, recorded as SPK45@SNK-20%.
[0046] The proton conductivity of the composite membrane 3 was tested using an electrochemical workstation. At 80°C and 100% relative humidity, the proton conductivity was 0.139 S cm -1 .
[0047] Example 4
[0048] A low-sulfonation degree SPEEK@sulfonic acid-rich porous organic framework composite proton exchange membrane was prepared. The preparation process was basically the same as that in Example 1, with the only difference being that in step 3, the mass ratio of SNK-41 dispersion to SPEEK dispersion was changed from 0.4:1 to 0.1:1 to finally obtain SPEEK@SNK composite membrane 4, recorded as SPK45@SNK-10%.
[0049] The proton conductivity of composite membrane 4 was tested using an electrochemical workstation. At 80°C and 100% relative humidity, the proton conductivity was 0.121 S cm -1 .
[0050] Comparative Example 1
[0051] Preparation of SPEEK proton exchange membrane, the specific steps include:
[0052] Step 1, preparation of SPEEK: same as step 1 of Example 1.
[0053] Step 2: Preparation of SPEEK proton exchange membrane: Prepare the SPEEK prepared in step 1 and N,N-dimethylacetamide (DMAc) to a mass volume concentration of 120 mg mL -1 The dispersion was stirred at room temperature until completely dissolved. The dispersion was evenly dropped on a 5 cm × 5 cm glass plate by solution casting, dried in a vacuum oven at 60 ° C for 12 hours, then dried in a vacuum oven at 80 ° C for 12 hours, and finally annealed in a vacuum oven at 120 ° C for 3 hours. After cooling to room temperature, the composite membrane was peeled off from the glass plate with ultrapure water to obtain a SPEEK proton exchange membrane, which was recorded as SPK45.
[0054] The proton conductivity of SPK45 was tested using an electrochemical workstation. At 80°C and 100% relative humidity, the proton conductivity was 0.094S cm -1 .
[0055] Comparative Example 2
[0056] The preparation of high sulfonation degree SPEEK proton exchange membrane includes the following specific steps:
[0057] Step 1, preparation of high-sulfonation degree SPEEK: the sulfonation time in step 1 of Example 1 was changed from 55 min to 150 min. The sulfonation degree was changed from 45% to 68%.
[0058] Step 2, preparation of a SPEEK proton exchange membrane with a high degree of sulfonation: the same as step 2 in comparative example 1, to obtain a SPEEK proton exchange membrane with a high degree of sulfonation, denoted as SPK68.
[0059] The proton conductivity of SPK68 was tested using an electrochemical workstation. At 80°C and 100% relative humidity, the proton conductivity was 0.124 S cm -1 .
[0060] Comparative Example 3
[0061] Nafion @ 117 proton exchange membrane, at 80℃, 100% relative humidity, the proton conductivity is 0.151S cm -1 .
[0062] Table 1 shows the composite membrane preparation process conditions and the properties of the resulting composite membrane.
[0063] Table 1 Composite membrane preparation process conditions and properties of the obtained composite membrane
[0064]
[0065] In Table 1, A represents SNK-41 and B represents SPEEK.
[0066] From Table 1 and Appendix Figure 1 It can be seen from the performance of the embodiments and comparative examples that various performances of composite membranes 1 to 4 are significantly improved. By comparing embodiment 1 and comparative example 1, it can be concluded that at 80°C and 100% RH, the proton conductivity of embodiment 1 is increased by 73%, and the ion exchange capacity is increased by 20%. Compared with comparative example 2, the surface swelling rate of embodiment 1 is reduced from 136.2% to 11.7%. Therefore, the introduction of SNK-41 greatly increases the content of polar groups (such as sulfonic acid groups) in the membrane, which is caused by the enhanced electrostatic interaction between polar groups. This electrostatic interaction is conducive to connecting discrete ion clusters in the membrane to form long-range orderly proton transport channels. At the same time, the attached Figure 2 The results of the proton conductivity stability test of the composite proton exchange membranes obtained in Example 1 and Comparative Examples 1-3 show that the stability of composite membrane 1 (corresponding to SPK45@SNK-40%) is stronger than that of SPK membrane and is comparable to that of Nafion @ This is not only due to the low swelling rate of the low-sulfonated SPEEK matrix, but also due to the dimensional stability and chemical stability of the sulfonic acid-rich SNK-41.
[0067] In summary, the present invention uses low sulfonation degree SPEEK as a matrix and sulfonic acid group-rich porous organic framework material (SNK-41) as a filler to prepare a composite proton exchange membrane of SPK@SNK-X (X is the mass fraction of SNK-41 in SPEEK). SNK-41 contains a large amount of hydrophilic sulfonic acid groups, which easily form hydrogen bonds with water molecules, and enhance the adsorption of water molecules by the material. In addition, the doping of high specific surface area SNK-41 provides a richer pore structure in the membrane, changing the microscopic phase separation structure of the polymer. The orderly arrangement of the hydrophilic water structure in the membrane is controlled by regulating the doping amount of SNK-41, thereby realizing the regulation of the proton transmission channel, reducing the energy barrier in the proton transmission process and optimizing the proton transmission path, thereby improving the proton conductivity. In addition, the sulfonic acid group-rich porous organic framework has a low swelling rate at high humidity, and the composite proton exchange membrane composed of the low sulfonation degree SPEEK base membrane is able to have the characteristics of high proton conductivity, high ion exchange capacity and low swelling rate.
[0068] The above are only several preferred embodiments of the present invention, but the present invention is not limited to the above several specific implementations. The above specific implementations are illustrative, not restrictive, and researchers in the field can make improvements and perfections under the guidance of the present invention and in accordance with the spirit and principles of the present invention, which are all within the protection scope of the present invention.
[0069] Matters not covered by the present invention are known technologies.
Claims
1. A method for preparing a low-sulfonation degree sulfonated polyetheretherketone-based composite proton exchange membrane, characterized by comprising the following steps: Step 1, Synthesis of sulfonic acid-rich porous organic framework (SNK-41): Take two reaction tubes, add acetonitrile and NK-COF-41 to reaction tube A, and add acetonitrile and 1,3-propane sultone to reaction tube B; under nitrogen protection, add the solution in tube B dropwise to tube A, and then reflux in a 60-80°C water bath for 12-24 hours; filter the reaction product, wash the filter cake with acetonitrile, and vacuum dry to obtain a red powder solid, which is recorded as SNK-41; in, In reaction tube A, 200-300 mg of dried NK-COF-41 was added to every 10 mL of ultra-dry acetonitrile; in reaction tube B, 200-300 mg of 1,3-propane sultone was added to every 10 mL of ultra-dry acetonitrile; the mass ratio of NK-COF-41 to 1,3-propane sultone was 4:5; Step 2, ball-milling the SNK-41 powder obtained in step 1, sieving it, adding it into N,N-dimethylacetamide (DMAc), and ultrasonically dispersing it to obtain a SNK-41 dispersion; Among them, 380-480 mg of SNK-41 powder was added to every 4 mL of DMAc; Step 3, adding the SNK-41 dispersion obtained in step 2 dropwise into the low-sulfonation-degree SPEEK dispersion, and stirring and mixing at room temperature to obtain a mixed solution; The concentration of SPEEK dispersion is 100-120 mg mL -1 , the solvent is DMAc; the mass ratio is, SNK-41 dispersion: SPEEK dispersion = (0.1-0.4): 1; Step 4, coating the mixed solution obtained in step 3 on a glass plate, vacuum drying at 40-60° C. for 6-24 hours, then vacuum drying at 70-90° C. for 12-24 hours, and finally annealing in a vacuum drying oven at 110-120° C. for 3-6 hours; after cooling to room temperature, peeling the composite membrane from the glass plate with ultrapure water to obtain a sulfonated polyetheretherketone / sulfonic acid-rich porous organic framework composite proton exchange membrane.
2. The method for preparing a low-sulfonation-degree sulfonated polyetheretherketone-based composite proton exchange membrane according to claim 1, characterized in that: The NK-COF-41 is obtained by vacuum drying after ball milling; the rotation speed of the ball mill is 500-1000rpm, and the time is 5-18h; the drying temperature is 40-80℃, and the time is 6-24h.
3. The method for preparing a low-sulfonation degree sulfonated polyetheretherketone-based composite proton exchange membrane according to claim 1, characterized in that: The thickness of the sulfonated polyetheretherketone / sulfonic acid group-rich porous organic framework composite proton exchange membrane is 16-60 μm.
4. The method for preparing a low-sulfonation degree sulfonated polyetheretherketone-based composite proton exchange membrane according to claim 1, characterized in that: The sulfonated polyetheretherketone / sulfonic acid-rich porous organic framework composite proton exchange membrane has a proton conductivity of 0.121S cm at 80°C and 100% RH. -1 -0.163S cm -1 .
5. The method for preparing a low-sulfonation degree sulfonated polyetheretherketone-based composite proton exchange membrane according to claim 1, characterized in that: The sulfonation degree of the low-sulfonation-degree SPEEK is 45%-55%.
Citation Information
Patent Citations
Polymethylacrylic acid filled imidazole microcapsule-sulfonated polyether-ether-ketone composite membrane and preparation method thereof
CN104059328A
SPEEK / MIL101 loaded phosphotungstic acid hybrid membrane, preparation and application
CN105670018A
Composite proton exchange membrane and preparation method thereof
CN110676496A
Composite proton exchange membrane as well as preparation method and application thereof
CN117219800A
Sulfonated polyetheretherketone-zirconium-based metal organic framework composite membrane as well as preparation method and application thereof
CN117820697A
Cited By
Preparation method of non-fluorine composite proton exchange membrane
CN122124632A